Perlindungan Hak Waris Perempuan Dalam Sistem Kekerabatan Patrilineal Berdasarkan Putusan Nomor 151/Pdt.G/2020/Pn Jkt.PstPerlindungan Hak Waris Perempuan Dalam Sistem Kekerabatan Patrilineal Berdasarkan Putusan Nomor 151/Pdt.G/2020/Pn Jkt.Pst - Rayi Kharisma Rajib; Alicia Angelica Asmara Putri; Helena Adinda Nabila (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to examine, review, and discuss the protection of women's inheritance rights in the patrilineal kinship system based on Decision Number 151/Pdt.G/2020/PN.Jkt Pst, especially regarding judges' considerations in granting inheritance rights to women in the midst of a patrilineal system that traditionally prioritizes men. This research is a normative juridical type based on an analysis of court decisions relevant to the issues discussed and uses a case study approach. The primary legal material in this study is in the form of court decisions, and is supported by Supreme Court jurisprudence related to the recognition of women's rights in customary inheritance law, while secondary legal materials are obtained from various literature such as books, scientific journals, articles, and other electronic sources relevant to the research topic. The research results show that in the decision, the judge did not solely adhere to the provisions of patrilineal customary law, but also considered the principles of justice, equality, and legal expediency. This ensures that women are still included as heirs and granted inheritance rights as biological children, even within a patrilineal kinship system. This demonstrates an effort to adapt customary law to the dynamic developments of society. If customary provisions conflict with the principles of justice and equality, they can be set aside to ensure fair legal protection for women.